Laparoscopic Primary Crural Repair for Acute-on-Chronic Organoaxial Gastric Volvulus Secondary to a Type II Paraesophageal Hernia: A Case Report and Review of Surgical Strategy - Danu Adi Prakosa Darmawan; Agung Aji Prasetyo; Ahmad Fathi Fuadi; Dimas Erlangga Nugrahadi (HM Publisher, 2025)
Background: Gastric volvulus, an abnormal rotation of the stomach, is a rare surgical emergency that can lead to life-threatening gastric ischemia and perforation, particularly when associated with a large paraesophageal hernia (PEH). While paraesophageal hernias are the most common predisposing factor in adults, the optimal surgical management, especially regarding the use of fundoplication and gastropexy, remains a subject of debate. Case presentation: We present the case of a 46-year-old male with a six-month history of intermittent epigastric pain and early satiety, who presented with a three-week history of acute-on-chronic gastric outlet obstruction. His symptoms included intractable postprandial vomiting. Laboratory findings were significant for hemoconcentration and a hypochloremic, hypokalemic metabolic state, indicative of severe dehydration. A contrast-enhanced computed tomography scan confirmed a Type II PEH with an organoaxial gastric volvulus, causing complete obstruction. Following aggressive resuscitation, the patient underwent successful laparoscopic surgery. The procedure involved reduction of the herniated and volvulized stomach, complete excision of the hernia sac, and a primary posterior crural repair with pledgeted, non-absorbable sutures. A fundoplication or gastropexy was not performed. Intraoperative endoscopy confirmed successful de-rotation, a patent pylorus, and viable gastric mucosa. The patient had an uneventful recovery and remained asymptomatic with no evidence of reflux at a six-month follow-up. Conclusion: This case highlights the classic